Cloud Computing a nivel de Software para internet de las cosas (IOT) - Campoverde Marca, Ariel Mauricio (2015)
One of the components of a telemetry system based on Internet of Things (IoT) is Cloud Computing, which consists of one or multiple interconnected servers that involve hardware and software to provide monitoring and control services. This paper shows a SaaS (Software as a Service) Cloud Computing structure for IoT by applying chosen open source tools based on a technical study whose results were validated by implementing a real time dashboard. The objective of this work is to define a Cloud-level structure that allows to deploy any application involved in IoT. For this purpose, current open source tools being adopted by the scientific community were analyzed and then those ones which better fit for restricted resources environments were selected, typical of wireless sensor networks (WSN).